The psychology of baseball inside the mental game of the major league player - Stadler, Michael A. (Gotham Books, 2007)
Psychologist Stadler goes beneath the surface of the game to explore the psychology behind the actions of the game's greats. He begins with the mind's role in the game's basic skills, explaining the anticipatory thinking that can make a hitter see a "rising fastball," the complex muscular coordination required to throw a major league heater, and the intense spatial calculations the brain must perform in a split second in order for a fielder to catch a struck ball. He then discusses the hidden nature of streaks and slumps, explaining why a "hot" hitter is most likely just getting lucky and why there's no such thing as a clutch hitter. He also looks at the psychological basis of the so-called "sophomore slump" and the effect that a big-money contract has on a player's performance, and explains what traits are most associated with success at the highest levels.--From publisher description.